Effects on walking performance and lower body strength by short message service guided training after stroke or transient ischemic attack (The STROKEWALK Study): a randomized controlled trial. (February 2021) - Vahlberg, Birgit; Lundström, Erik; Eriksson, Staffan; Holmbäck, Ulf; Cederholm, Tommy
Objective: To evaluate whetherdaily mobile-phone delivered messages with training instructions during three months increase physical activity and overall mobility in patients soon after stroke or transient ischemic attack. Design: Randomised controlled trial with intention-to-treat analyses. Setting: University hospital. Data collection from November 2016 until December2018. Subjects: Seventy-nine patients (mean (SD) age 63.9 (10.4) years, 29 were women) were allocated to either intervention ( n = 40) or control group ( n = 39). Participants had to be independent (modified Ranking Scale ⩽2) and able to perform the six-minute walking test at discharge from the hospital. Interventions: The intervention group received standard care and daily mobile phone instructional text messages to perform regular outdoor walking and functional leg exercises. The control group received standard care; that is, primary care follow-up. Main measures: Walking performance by six-minute walking test (m), lower body strength by five times chair-stand test (s), the short physical performance battery (0–12 points) and 10-metres walk test (m/s) were assessed at baseline and after three months. Results: The estimated median difference in the six-minute walking test was in favour of the intervention group by 30 metres (95% CI, 55 to 1; effect size 0.64; P = 0.037) and in the chair-stand test by 0.88 seconds (95% CI, 0.02 to 1.72; effect size 0.64; P = 0.034). There were no differences between groups on the short physical performance battery or in 10-metres walking time. Conclusions: Three months of daily mobile phone text messages with guided training instructions improved composite mobility measures; that is, walking performanceand lower body strength. Clinical Trial Registry: The study is registered withClinicalTrials.gov, number NCT02902367.